SPA14 liposomes combining saponin with fully synthetic TLR4 agonist provide adjuvanticity to hCMV vaccine candidate - Ernesto Luna; Sophie Ruiz; Marie Garinot; Cyril Chavagnac; Pankaj Agrawal; John Escobar; Laurent Revet; Marie-Jeanne Asensio; Fabienne Piras; Francis G. Fang; Donald R. Drake; Bachra Rokbi; et al. (npj Vaccines)
Abstract In the aim of designing and developing a novel saponin-based adjuvant system, we combined the QS21 saponin with low microgram amounts of the fully synthetic TLR4 agonist, E6020, in cholesterol-containing liposomes. The resulting adjuvant system, termed SPA14, appeared as a long-term stable and homogeneous suspension of mostly unilamellar and a few multilamellar vesicles, with an average hydrodynamic diameter of 93 nm, when formulated in citrate buffer at pH 6.0-6.5. When compared in an in vitro human innate immunity construct to AS01B, the QS21/MPL® liposomal adjuvant system of GSK, and with QS21-Liposomes used as benchmarks, SPA14 displayed the strongest immunostimulatory potential based on antigen-presenting cell (APC) activation and cytokine secretion, which was essentially driven by the highly active E6020 agonist in this assay. When tested as an adjuvant in vivo with human cytomegalovirus glycoprotein B (gB) and pentamer complex (PC) as test antigens, SPA14 was generally well tolerated and as active as AS01B for the induction of long-lasting CMV-neutralizing antibodies in mice and non-human primates (NHPs). Both adjuvants promoted the induction of Th-1 responses based on IgG2c production in mice and IFN-γ production in mice and NHPs, but in mice, a higher level of Th-2 cytokines (IL-5) and higher IgG1 over IgG2c secreting cells ratios were obtained with SPA14 indicating that the adjuvant profile of SPA14 could be less Th-1 biased than that of AS01B. From a developability standpoint, SPA14 could be manufactured by a simple and scalable ethanol injection method, owing to the high solubility in ethanol of all its lipidic components, including E6020. Furthermore, E6020 is a single molecule, well-characterized fully synthetic TLR4 agonist constructed in eight synthetic steps from entirely crystalline starting materials and intermediates via an optimized high-yield synthetic route. Overall, our data suggest that SPA14 is a viable, easy-to-manufacture, potent novel adjuvant system that could be broadly applicable as a ready-to-mix adjuvant in the form of a long-term stable liquid formulation.